Alternative production of craft lager beers using artichoke (Cynara scolymus L.) as a hops substitute - Schuina, Guilherme Lorencini [UNESP]; Quelhas, João Olavo Figueiredo [UNESP]; de CASTILHOS, Maurício Bonatto Machado; de CARVALHO, Giovani Brandão Mafra; Del Bianchi, Vanildo Luiz [UNESP] (FapUNIFESP (SciELO), 2020)
Beer is a fermented beverage made from barley malt and hops under the action of a suitable yeast. The main function of hops in the brewing process is to provide bitterness, characteristic flavours and aromas to the beverage. However, hops only began to be added to the formulation of this beverage starting in the ninth century. Therefore, the use of other bitter plants as a substitute for hops may be a viable alternative. This study aimed at evaluating the use of artichoke as a total substitute for hops in American lager craft beer production. The substitution of hops with up to 2 g⋅L-1 artichoke resulted in a beer with a quality similar to that of the American lager beer traditionally found in the market. So, artichoke was confirmed to be a viable alternative for hops, having satisfactory physicochemical characteristics and good sensorial acceptance.
Keywords: Bitter plants; Bitterness; Brewing